Determinants, advantages and threats resulting from application of the relationship marketing concept and CRM technology in maintaining customer Loyalty in Travel Offices in Poland = Zastosowanie koncepcji marketingu relacji oraz technologii CRM w utrzymaniu lojalności klientów biur podróży w Polsce - Rapacz, Andrzej; Michalska-Dudek, Izabela (Zielona Góra: Faculty of Economics and Management Press)
In this paper, there are presented both the essence of the relationship marketing concept and the characteristics of CRM class systems, as well as basic advantages and threats resulting from their implementation. There are also described results of the questionnaire survey, which estimated the awareness and level of application of marketing relationship concept and CRM technology in functioning of travel offices in Poland. Conducted survey results allowed for an assessment of the crucial component of the study becomes an identification of benefits and concerns related to implementing these solutions by travel offices.
Keywords: marketing relacji; system klasy CRM; biura podróży; relationship marketing; CRM system; travel office